Organizational aspects of digital transformation of construction processes - DUBININ, Denis; CHERTKOV, Oleg (Ways to Improve Construction Efficiency, 2024)
The article examines the organizational aspects of the digital transformation of construction processes, which is a relevant issue for increasing the efficiency and competitiveness of the construction industry, analyzes current trends in the implementation of digital technologies in construction, their impact on project management, cost optimization, risk reduction and improvement of the quality of construction work.Particular attention is paid to organizational challenges that arise during the implementation of digital solutions. Among them, the need to change management approaches, adapt corporate culture, train personnel with appropriate digital competencies, as well as integrate new technologies into existing organizational and technological processes, as well as construction administration and management processes, is highlighted, it is emphasized that digital transformation encompasses not only the implementation of information technologies, but also requires a strategic approach to change management at the level of individual construction participants.The use of BIM (Building Information Modeling), IoT (Internet of Things), process automation, digital platforms for project management and cloud services is also considered. The advantages of using these tools are analyzed, in particular, increasing transparency and speed of communication between project participants, accuracy of design calculations and reduction of waste in construction.Practical recommendations are provided for the formation of an effective digital transformation strategy for construction companies. The main stages are proposed: assessing the readiness of construction participants for change, determining priority areas of automation, developing a roadmap for the implementation of digital technologies and monitoring results. The importance of an interdisciplinary approach is emphasized, which includes close cooperation between managers, engineers, IT specialists and estimators. It is noted that successful digitalization is possible only with support from management, involvement of employees in the change process and investment in modern software and technical equipment.